Residents’ participation in energy performance certification for collective action on climate change: the case of EnerGuide - Chen, Xinyu; Gou, Zhonghua; Zhang, Huihua (Frontiers in Psychology, 2023)
Introduction Although governments have launched energy performance certification (EPC) programs to increase residential energy efficiency, residents’ perception and acceptance of these programs have been little studied. This study contextualizes residents’ intentions to participate in EPC programs in terms of their attributions to and attitudes toward climate change to find mediating factors and effects to help trigger collective action to reduce residential sector energy demand. Methods This study employed a partial least squares structural equation modeling approach to empirically analyze a survey conducted on 400 residents of Edmonton, Canada, who participated in the Canadian energy efficiency rating and labeling program, EnerGuide. Results and Discussion Using EnerGuide, a Canadian energy efficiency rating and labeling program, as an example, this study establishes a framework to explain that local residents’ internal and external attributions to climate change elicit positive attitudes (need to take action), increasing their recognition of energy efficiency program benefits, which further promotes their EnerGuide program acceptance and participation intentions. This study also reveals the mediating effects between variables. Residents’ attitudes toward climate change mediate the relationship between internal/external attributions and EnerGuide program acceptance, and they indirectly impact residents’ program acceptance and participation intentions, with this effect moderated by energy efficiency program benefits. Residents’ program acceptance also mediates the relationship between climate change attitudes/energy efficiency program benefits and the intention outcome. Implication The study provides an example of the use of climate change discourse to motivate residents’ energy efficiency program participation.